Perceptions on Regulation and Asymmetry of Information as Critical Factors in University Governance in Latin America - Abello-Romero, J (SAGE Publications Inc., 2021)
This article analyzes the results of an inquiry into Latin American university community members’ perceptions about regulatory processes and asymmetries of information, as influential factors in the governance of Latin American universities. It does so, by examining the national laws in Argentina, Brazil, Colombia, Chile, and Mexico. Previous studies in this continent have not considered these aspects and perspectives. Our research found significant differences between countries in terms of the Board of Directors’ capacity to act and the control mechanisms they can employ—which can be interpreted as national differences in the availability of their resources and their regulatory capacities. On the level of asymmetry of information, there are differences between countries, which depend on the position of the university members in their institutions. Thus, regulation and information are important factors when it comes to the governance of Latin American universities, and can explain its’ diversity. © The Author(s) 2021.